Delayed diagnosis of sarcoidosis is common in Brazil - Rodrigues, Mauri Monteiro (2013)
OBJECTIVE:To determine the frequency of and the factors related to delayed diagnosis of sarcoidosis in Brazil.METHODS:We evaluated patients with a biopsy-proven diagnosis of sarcoidosis, using a questionnaire that addressed the following: time since symptom onset and since the first medical visit; and the number and specialty of the physicians visited. We divided the patients by the timeliness of the diagnosis-timely (< 6 months) and delayed (≥ 6 months)-comparing the two groups in terms of systemic and pulmonary symptoms; extrathoracic involvement; spirometric data; radiological staging; level of education; income; and tuberculosis (diagnosis and treatment).RESULTS:We evaluated 100 patients. The median number of physicians consulted was 3 (range, 1-14). In 11 cases, sarcoidosis was diagnosed at the first visit. In 54, the first physician seen was a general practitioner. The diagnosis of sarcoidosis was timely in 41 patients and delayed in 59. The groups did not differ in terms of gender; race; type of health insurance; level of education; income; respiratory/systemic symptoms; extrathoracic involvement; and radiological staging. In the delayed diagnosis group, FVC was lower (80.3 ± 20.4% vs. 90.5 ± 17.1%; p = 0.010), as was FEV1 (77.3 ± 19.9% vs. 86.4 ± 19.5%; p = 0.024), misdiagnosis with and treatment for tuberculosis (≥ 3 months) also being more common (24% vs. 7%, p = 0.032, and 20% vs. 0%; p = 0.002, respectively).CONCLUSIONS:The diagnosis of sarcoidosis is often delayed, even when the imaging is suggestive of sarcoidosis. Delayed diagnosis is associated with impaired lung function at the time of diagnosis. Many sarcoidosis patients are misdiagnosed with and treated for tuberculosis.